A geomechanical model for predicting the collapse of a carbonate formation - Avilés Hilario, Ulises Sholl (My University, 2025)
It is a study where a Time-Implicit model is developed to predict the collapse of a carbonate formation in a mature field using reservoir data from Indiana, USA. There are case studies in the literature where sand control and prediction methods are applied to carbonate formations due to the limited information available for the latter. In this work, the prediction method using a hydromechanical model for sands (Stavropoulou, Papanastasiou, & Vardoulakis, 1998) evaluating its reliability in carbonates formations.
Wellbore instability is one of the significant challenges in drilling engineering and during the development of carbonate reservoirs, especially with open-hole completions during depletion; it can cause a reduction in permeability, damage to the equipment, solids production, and wellbore failure, interrupting production and affecting the reservoir's ultimate recovery. Therefore, it is essential to have a numerical tool to predict the conditions that may cause major solids production problems to prevent collapse
Keywords: Rock Mechanics; Formation collapse; Time-Implicit Numerical Model; Solids Production; Carbonates formation